Pelatihan Pengolahan Bambu di Desa Jatibatur Kabupaten Sragen - Munawaroh, Anik; Trihastuti, Ratna (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this community service activity is to train the community to process bamboo in Jatibatur Village, Sragen Regency. The methods used include: 1) approach to the community as the initial stage of activity; 2) training for the community on how to market handicraft products in the current conditions; 3) make observations to find out the problems that exist in the local community; and 4) conducting training to the community to increase productivity levels. The results of the activities that have been carried out are making several cleaning activities, and participating in mutual cooperation with local residents in order to establish closeness to the community so that it is easier to carry out an activity. The residents, the head of the village head and his staff took part in the counseling activities held by the community service implementation team with the theme "Bamboo Processing Training", explaining to the public how to market post-pandemic handicraft products. Another outcome is training to the public on management and marketing techniques in order to enhance marketing promotions.